Influence of breeding and length of feeding period on carcass characteristics and palatability of beef - Mackintosh, D.L.; Kropf, Donald H.; Harrison, D.L.; Moore, E.R.; Ahlschwede, G. (Kansas Agricultural Experiment Station, 2011)
Sixty-four steer calves owned by Martin K. Eby and sired by the same bull were selected randomly from the 1962 fall calf crop. The calves were randomly selected and sorted into eight groups and placed in the feedlot. The first group was shipped to Kansas City for slaughter. Fifty-six days later Lot 2 was shipped and each 28 days thereafter eight steers were slaughtered for dressing and carcass data.
Keywords: Meat; Carcass characteristics; Palatability; Marbling